2018
DOI: 10.1002/biot.201700478
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Gas Enhanced Oil Recovery in Multiphase Fermentations for the Microbial Production of Fuels and Chemicals

Abstract: In multiphase fermentations where the product forms a second liquid phase or where solvents are added for product extraction, turbulent conditions disperse the oil phase as droplets. Surface-active components (SACs) present in the fermentation broth can stabilize the product droplets thus forming an emulsion. Breaking this emulsion increases process complexity and consequently the production cost. In previous works, it has been proposed to promote demulsification of oil/supernatant emulsions in an off-line bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This is especially true for bulk products like biofuels. 70,71 Additionally, 2-undecanone has a log P of 4.1. This is in the lower range of the log P values that most microorganisms can tolerate for growth.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially true for bulk products like biofuels. 70,71 Additionally, 2-undecanone has a log P of 4.1. This is in the lower range of the log P values that most microorganisms can tolerate for growth.…”
Section: Resultsmentioning
confidence: 99%
“…The highest oil recovery was observed for F4 (88% clear oil release), yet this cannot be fairly compared against the other cases, since the early CaCl 2 addition had an impact on fer-mentation performance and oil emulsification. Surprisingly, the results showed that F4 had higher protein concentration (see Table 7), which has been reported to increase emulsion stability (Heeres et al, 2014;Heeres et al, 2015;Pedraza-de la Cuesta et al, 2017). Studies reported CaCl 2 as a cross linking agent (Hariyadi et al, 2014;Ye and Singh, 2000) which can promote protein bridging making the emulsion more susceptible to the shear by centrifugation and promoting oil recovery.…”
Section: Impact Of Flocculants In Oil Recovery By Centrifugationmentioning
confidence: 94%
“…The impact of flocculants in enhancing oil recovery by GEOR was assessed in the aforementioned fermentations and synthetic emulsion. The reproducibility of fermentations allows to exclude important parameters, such as oil fraction and biomass concentration, that can influence GEOR's performance and results (Heeres et al, 2016;Pedraza-de la Cuesta et al, 2017). The same cannot be held for fermentation F4.…”
Section: Impact Of Flocculants In Oil Recovery By Geormentioning
confidence: 99%
See 2 more Smart Citations